A Bibliometric Analysis of Best Practices on the Role of Government in Sustainability and Environmental Management - Loso Judijanto; Afif Syarifudin Yahya; Iwan Harsono; Anisa Fitria Utami (West Science Social and Humanities Studies, 2024)
This bibliometric analysis delves into the extensive body of literature on the role of government in sustainability and environmental management, addressing the imperative for sustainable development amidst increasing environmental challenges. Through a systematic exploration of scholarly publications, the study identifies clusters of literature, research trends over time, and potential areas for future investigation. The analysis reveals key thematic areas, including Corporate Social Responsibility (CSR) and Governance, Waste Management, Environmental Governance, Energy and Innovation, and Supply Chain Sustainability. Top-cited research studies and the visualization of term occurrences offer foundational insights for policymakers and researchers. The findings emphasize the evolving priorities in the field and underscore the need for interdisciplinary collaboration to address complex challenges. Overall, the study contributes to a nuanced understanding of best practices, guiding stakeholders in formulating evidence-based policies for sustainable development.